Pendidikan Agama Islam (PAI) untuk Membentuk Perilaku Bertanggung Jawab dalam Konsumsi dan Produksi bagi Generasi Muda - Muhammad Muslim Jauhari; Intan Pertiwi Ahmad; Lailatul Isti'anah (FKIP UNSULTRA, 2025)
The consumption and production behavior of today's young generation faces significant challenges due to lifestyle changes, a culture of instant consumption, and digital penetration that encourages unsustainable lifestyles. In this context, Islamic Religious Education (PAI) plays a strategic role in shaping students' character, fostering moral awareness, ethics, and social responsibility in managing resources. This literature review aims to examine the concepts, values, and approaches within PAI that contribute to the formation of responsible behavior in consumption and production. The analysis was conducted on various academic sources, including journals, books, and empirical research related to values ​​education, Islamic ethics, sustainability, and ecological behavior. The results of the review indicate that PAI contains fundamental principles such as islah (improvement), tawazun (balance), i'tidal (moderation), amanah (responsibility), and khilafah (earth stewardship) that are relevant in encouraging ethical consumption behavior and sustainable production. Implementation of these values ​​can be achieved through curriculum integration, contextual learning, teacher role models, and behavioral habituation through ecological activities. This study concludes that Islamic Religious Education (PAI) has significant potential in developing a young generation that is not only religious but also imbued with a sustainable perspective. Therefore, strengthening the Islamic Religious Education (PAI) curriculum based on sustainability values ​​is a strategic urgency to address global challenges related to the environmental crisis, resource waste, and consumer behavior. Further research is recommended to develop a more systematic and measurable model for implementing environmentally friendly Islamic Religious Education (PAI).